Edible Molluscs of West Bengal and Their Role in Human Health: A Review - Souvik Bisui; Rita Mondal; Ranajit Kumar Khalua (The Bioscan, 2026)
Edible molluscs constitute an important component of aquatic biodiversity and traditional diets in many coastal and freshwater regions of India, including West Bengal. Molluscs such as snails, clams, oysters, and mussels are widely consumed by local communities due to their high nutritional value and availability in rivers, ponds, wetlands, and coastal ecosystems like the Sundarbans. These organisms provide high-quality proteins, essential amino acids, polyunsaturated fatty acids, vitamins, and minerals that support human health and nutrition. In addition, molluscs contain several bioactive compounds that possess therapeutic and nutraceutical properties. The present review discusses the diversity of edible molluscs found in West Bengal, their nutritional composition, and their role in promoting human health. The review also highlights their traditional consumption, economic significance, and potential for sustainable food systems and functional food development.